2017
DOI: 10.1136/bcr-2016-218328
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of new-onset psychotic disorder following recovery from LGI1 antibody-associated limbic encephalitis

Abstract: Neuronal autoantibodies targeting cell surface antigens have been described in association with autoimmune encephalitides which frequently feature psychosis and other psychiatric disturbances alongside neurological signs and symptoms. Little has been written however about the long-term psychiatric status of individuals following recovery from the acute phase of autoimmune encephalitis, despite case series and anecdotal evidence suggesting this may be a cause of considerable disability. Here, we describe a man … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…There are autoimmune encephalopathies characterized by their chronic relapse-remitting character, such as GAD65 autoimmune encephalitis (Hansen et al 2018 ), which probably disturbs brain function and structure repeatedly and may lead to permanent deficits resulting in the manifestation of psychiatric disease. Furthermore, a recent report suggested that a patient who recovered from LGI1- encephalitis developed a new onset psychotic disorder after surviving a one-year course of LGI1-antibody-positive encephalitis (Pollak and Moran 2017 ). This is a paradigmatic example of how a subsiding or chronic, recurrent autoimmune encephalitis with circulating serum or cerebrospinal fluid autoantibodies may influence psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…There are autoimmune encephalopathies characterized by their chronic relapse-remitting character, such as GAD65 autoimmune encephalitis (Hansen et al 2018 ), which probably disturbs brain function and structure repeatedly and may lead to permanent deficits resulting in the manifestation of psychiatric disease. Furthermore, a recent report suggested that a patient who recovered from LGI1- encephalitis developed a new onset psychotic disorder after surviving a one-year course of LGI1-antibody-positive encephalitis (Pollak and Moran 2017 ). This is a paradigmatic example of how a subsiding or chronic, recurrent autoimmune encephalitis with circulating serum or cerebrospinal fluid autoantibodies may influence psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…In other infection-induced psychoses, the production of autoantibodies has been noted [ 19 ]. However, this appears to be a less likely cause of psychosis in this patient, given the short timescale in which his symptoms resided once Brucella had been eradicated.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, primary HCWs-based models are effective, feasible, and scalable for integrative care, including screening, monitoring, and referral care. These models effectively improve the screening of perinatal women for depression using the Patient Health Questionnaire (PHQ-2 or PHQ-9) in tertiary care settings 13 and can be included as community-based assessments (e.g., Community Based Assessment Checklist in India) and part of national programs. 14 However, there are various challenges for the implementation of these interventions/models in resource-limited settings, including limited training resources, overburdened primary HCWs with multiple responsibilities under different programs, and difficulty maintaining records and arranging follow-ups.…”
Section: Approaches To Reduce the Treatment Gapmentioning
confidence: 99%